LOS JÃ“VENES UNIVERSITARIOS Y EL OCIO - Pascucci, Marisa (European Scientific Journal, ESJ, 2015)
This paper is a brief summary of the Doctoral Thesis "Benefits of leisure activities of university students from the University of Flores, Regional Comahue". Through it, we tried to help give birth to the concept of leisure from an empirical basis and within the framework of a specific population. A questionnaire where the various components of leisure concept were reported in the literature were included; and the questionnaire was applied to a sample of universities. This study helps us to determine whether the frequency of leisure practices performed by university students from the University of Flores, Regional Comahue, contributes to the increased perception of general well-being both at the physical, psychological, social, and spiritual level. Through this theoretical and field research, we try to review the literature previously available on the subject, studied the leisure of the selected population, and framed in positive psychology that takes the study of Seligman and Csikszeritmihalyi as a reference point.